SERTULUM DIPTEROCARPACEARUM MALAYENSIUM-VII - D. F. VAN SLOOTEN (REINWARDTIA, 1961)
Critical notes, emended descriptions, and considerations on synonymy have been given of 8 species of Dipterocarpus, 1 of Dryobalanops, 1 of Parashorea, and 2 of Vatica. Vatica imbricata. van Slooten is referred to Kayea (Guttiferae). Three species of Dipterocarpus have been described as new, viz D. sarawakensis and D. tempehes from Borneo and D. ursinus from Sumatra. There is one new combination, Hopea forbesii (Brandis) Van Slooten, based on Shorea forbesii Brandis.